Inflationary dark energy from a condensate of spinors in a 5D vacuum - Bellini, Mauricio (2013)
What is the physical origin of dark energy? Could this energy be originated by other fields than the inflaton? In this work we explore the possibility that the expansion of the universe can be driven by a condensate of spinors. These spinors are free of interactions on 5D relativistic vacuum in an extended de Sitter spacetime. The extra coordinate is considered as noncompact. After making a static foliation on the extra coordinate, we obtain an effective 4D (inflationary) de Sitter expansion which describes an inflationary universe. In view of our results we conclude that the condensate of spinors here studied could be an interesting candidate to explain the presence of dark energy in the early universe.